The Urgency of Judge's Legal Reasoning in Deciding on an Environmental Crime Case Based on an Ecocentric Approach (Review of Case Decision No. 640/PID.B/LH/2021/PT PBR) - Ainun Jiwanti; Eko Soponyono (Universitas Muhammadiyah Surakarta, 2022)
Objective: This study aims to analyze how the legal reasoning of the Pekanbaru High Court Judge in Decision No. 640/PID.B/LH/2021/PT PBR, and at the same time reviewing decisions at the previous level and show how important the judge's legal reasoning is based on an ecocentric approach in deciding environmental crime cases. Methods: This type of research is a normative law using statutory, case, and conceptual approaches. Findings: The panel of judges of the Pekanbaru High Court granted the defendant's appeal, PT. Gandaerah Hendana because Article 98 paragraph (1) of the PPLH (Environmental Protection and Management) Law that the public prosecutor indicted is a material offense that must be linked to its formal elements (Article 108 of the PPLH Law). It differs from the opinion of the Rengat District Court panel of judges, which stated that because the meaning of